Odpowiedzi

2010-01-16T15:59:51+01:00
A. 2x^-5x^+2xy^-xy^=-3x^+xy^=3*[1/3]^+1/3*9^=3*1/6+1/3*81=1/2+27=27 i 1/2
b.-2/3xy+1/3xy=1/2x³y+1/2x³
-1/3xy=1/54*9+1/54
-1=10/54 eee....
3 1 3
Najlepsza Odpowiedź!
2010-01-16T16:24:00+01:00
A) 2x²-xy²- 5x²+2xy²= -3x²+xy²= -3(⅓)² + (⅓)×9²= -⅓ + (⅓)×81= (-⅓) + 27= 26⅔

b) (-½)x³y-(⅔)xy= (½)x³-(⅓)xy
(-⅔)xy+(⅓)xy= (½)x³+ (½)x³y
(-⅓)xy= (½)x³+ (⅓)x³y
(-⅓)×(⅓)×9= (½)×(⅓)³+ (⅓)×(⅓)³×9
(-⅓)× 9 = (½)×(¹/₂₇) + (⅓)×(¹/₂₇)×9
-1= (¹/₅₄)+(¹/₉) ×3
-1= (¹/₅₄)+ (⅓)
-1= (¹/₅₄)+ (¹⁸/₅₄)
-1= (¹⁹/₅₄)

Drugie równianie jest sprzeczne!!!
4 4 4